ANALISIS PARAMETER AIR LIMBAH INDUSTRI PENYAMAKAN KULIT SUKAREGANG GARUT - Astri Senania; Novi Yanti (Lantanida Journal, 2022)
The leather tanning industry of Sukanggang Garut is an industry that has the potential to produce wastewater that contains a lot of organic substances. Therefore, it is necessary to conduct an effective test to determine the parameters of wastewater pollution in the leather tanning industry. The purpose of this study was to test the value of water pH, Chemical Oxygen Demand (COD), Biochemical oxygen Demand (BOD), Total Suspended Solid (TSS), and the amount of chromium concentration in the sample taken. The BOD test will be carried out using the Winkler method, the COD test will be carried out using the reflux method and the TSS test will be carried out using the gravimetric method, while the chromium concentration test will use an AAS spectrophotometer and the pH test will be carried out using a pH meter. The test results show that the liquid waste from the tanning industry activity in Sukaregang Garut exceeds the liquid waste threshold for the leather tanning industry.